(untitled) (AmeriQuests)
In this age of stark polarization of American political opinion, learning to communicate effectively across party lines is more important than ever before. Mugambi Jouet’s Exceptional America sheds light on the political, social and cultural factors contributing to both the divide between America and the rest of the Western world and the divide between Americans themselves. However, merely understanding such factors is not enough. Translating these understandings into crucial conversations and using them to question our own beliefs is where the challenge lies. Luckily, there is hope: By thinking critically about political issues and embracing uncomfortable conversations with our adversaries, we can begin bridging this painful divide.